Tinjauan Bentuk dan Fungsi Musik pada Seni Pertunjukan Ketoprak Dor - Panji Suroso (Gondang: Jurnal Seni dan Budaya, 2018)
This article reviews the form and function of music at the Ketoprak Dor show that grew and developed in the land of Deli North Sumatra as a culture owned by the Javanese Deli community group. Departing from the phenomenon of the existence of the performance of Ketoprak Dor art in several areas inhabited by the majority of Javanese in the villages around Deli plantations, it led the author to begin to explore the problem of musical elements as one of the most important parts of this performance. Based on the study conducted by the author, it is indicated that the elements that form the Ketoprak Dor show have their own uniqueness, and can be distinguished from similar art in the island of Java. The forming elements of the show are: elements of dance, literature, fashion, stage, theater, motion and dance and elements of music have their own characteristics, and are very different from the ketoprak that is on the island of Java. On this occasion the author only specializes in the discussion of musical elements in the Ketoprak Dor performance art, which is about how the form of music and its function in the Ketoprak Dor performance art.